Development and characterization of jam from tambis (Syzygium aqueum) fruit. - Fantonalgo, Shaina Mae N.
Tambis (Syzygium aqueum) is a tropical fruit that is widely grown in the Philippines. Although tambis fruit is still underutilized and has limited commercial production in the country, developimg it into new products can increase its market value and at the same time extend the eating quality of fruits through preservation. This study intended to utilize the pale green tambis fruits in jam making. The tambis fruit was primarily evaluated for its physico-chemical properties and it obtained a moisture content of 91.56%, pH of 4.115, total soluble solids (TSS) of 6.98°Brix, titrable acidity (TA) of 0.325% citric acid, and pectin content of 0.95%. The three formulations of the tambis jam were prepared with varying fruit-to-sugar ratio: Formulation A (45:55), Formulation B (55:45) and Formulation C (65:35). Based on rank test for preference, Formulation B was chosen as the most preferred formulation. The MPF of tambis jam was characterized based on the physico-chemical properties and it showed that the jam had a pH of 3.585, TSS of 64.85°Brix, TA of 0.33% citric acid, and a viscosity of 1018.5 cP. The proximate composition of the MPF of tambis jam were 28.03% moisture content, 0.40% ash content, 0.026% crude protein, 0.075% crude fat, 2.21% crude fiber, and 69.26% carbohydrate content all in wet basis. Through sensory evaluation, the MPF of tambis jam was characterized as moderately brown, moderately sweet and easily spreadable. The general acceptability of the MPF of tambis jam was assessed through consumer testing. It was observed that the tambis jam has high acceptability among the consumers since 59% of the total respondents liked the product very much. Therefore it is concluded that the tambis jam has a commercial opportunity in the market.